P314 Effect of night work on sleep duration, sleep quality and sleep perception in a cohort of female nurses. (1st September 2016) - Langenberg, Daniella van de; Vlaanderen, Jelle; Pijpe, Anouk; Hartmann, Julia; Rookus, Matti; Vermeulen, Roel
Abstract : Background: Shift work has become an unavoidable part of our society; approximately 15-20% of the working population is working in shifts and this percentage is increasing. Sleep disruption is a common complaint among shift workers, especially night-shift workers. Night workers need to sleep at inappropriate moments within their circadian rhythm, which might result in sleep-related problems. Sleep-related problems have been associated with increased risk of cardiovascular disease, diabetes and all-cause mortality. Aim: In this study we aimed to determine the effect of night work on sleep duration and quality. In addition we aimed to determine which sleep-related aspects (including medication, chronotype, bedroom determinants, light exposure, and naps) contributed to a poorer sleep outcome in shift-working nurses. Methods: We used data from the Nightingale study, a prospective cohort study among female registered nurses. The analyses were conducted among 59, 947 participants who filled in a questionnaire distributed in 2011. Sleep quality was measured using the MOS sleep scale (0–100) and sleep quantity was defined as the average sleeping hours over four weeks. We assessed the association between working at night and sleep using linear regression models and explored potential interactions with other sleep related factors. Results: Preliminary results did not show a significant effect of working at night on sleep quantity (β 0.007, SE 0.010) and a small positive effect (β 0.867, SE 0.138) on sleep quality. Our findings indicate a confounding effect of chronotype on the association between working at night and sleep duration and quality. Conclusions: We did not find a relevant difference between night-shift workers and day workers for both sleep duration and sleep quality. The lack of difference might be explained by sleep-architecture details such as consolidation and other sleep-quality aspects which the MOS sleep scale did not cover, therefore studies using actigraphy and polysomnography data are recommended.